2016
DOI: 10.1371/journal.pone.0161205
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Ethanol Exposure Dysregulates BMP and Notch Signaling, Leading to Persistent Atrio-Ventricular Valve Defects in Zebrafish

Abstract: Fetal alcohol spectrum disorder (FASD), birth defects associated with ethanol exposure in utero, includes a wide spectrum of congenital heart defects (CHDs), the most prevalent of which are septal and conotruncal defects. Zebrafish FASD model was used to dissect the mechanisms underlying FASD-associated CHDs. Embryonic ethanol exposure (3–24 hours post fertilization) led to defects in atrio-ventricular (AV) valvulogenesis beginning around 37 hpf, a morphogenetic event that arises long after ethanol withdrawal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 65 publications
6
37
0
Order By: Relevance
“…Developmental timing of chemical exposure can be tightly controlled to examine stage-specific exposure effects; a simple dissecting microscope can provide information on cardiac edema; transparent embryos with transgene expression in the heart that allows for the use of stereomicroscope to quickly evaluate heart formation defects; and advanced imaging facilitates detail analysis at the cellular level (Figure 1A–I). Studies have recapitulated cardiac defects in zebrafish similar to those seen in human patients due to prenatal exposure of various teratogens [34,35,36]. High fecundity, rapid development outside the mother’s body, and well-characterized cardiogenesis stages combined with transparency enabling non-invasive, whole animal imaging make the zebrafish embryo an ideal model system for cardiac teratogenicity screens.…”
Section: Advantages Of Zebrafish In Cardiotoxicity Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Developmental timing of chemical exposure can be tightly controlled to examine stage-specific exposure effects; a simple dissecting microscope can provide information on cardiac edema; transparent embryos with transgene expression in the heart that allows for the use of stereomicroscope to quickly evaluate heart formation defects; and advanced imaging facilitates detail analysis at the cellular level (Figure 1A–I). Studies have recapitulated cardiac defects in zebrafish similar to those seen in human patients due to prenatal exposure of various teratogens [34,35,36]. High fecundity, rapid development outside the mother’s body, and well-characterized cardiogenesis stages combined with transparency enabling non-invasive, whole animal imaging make the zebrafish embryo an ideal model system for cardiac teratogenicity screens.…”
Section: Advantages Of Zebrafish In Cardiotoxicity Studymentioning
confidence: 99%
“…Ethanol withdrawal long before endocardial cushion formation led to valve defects. Following this study, Sarmah and colleagues combined state-of-the-art zebrafish transgenic lines that label myocardium and endocardium with various cardiac regulatory signaling reporter lines including Bmp, Notch, and Wnt signaling reporters, marker staining, and advanced microscopy to gain mechanistic insight into the etiology of ethanol-induced atrioventricular valve defects [36]. This study showed that ethanol exposure reduced Bmp signaling during early heart developmental stages.…”
Section: Toxic Substances Causing Heart Defects In Zebrafishmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with bone morphogenic protein signaling, proper localization of Notch signaling at the atrio-ventricular canal is necessary for cardiac valve morphogenesis. Changes in the distribution of Notch within this tissue compartment causes faulty valve development [79]. …”
Section: Boundary Regulation By Notch Signalingmentioning
confidence: 99%